Innate inflammatory responses of pediatric cystic fibrosis airway epithelial cells: Effects of nonviral and viral stimulation - Sutanto, E.; Kicic, Anthony; Foo, C.; Stevens, P.; Mullane, D.; Knight, D.; Stick, S. (American Lung Association, 2011)
There is controversy regarding whether cystic fibrosis (CF) airway epithelial cells (AECs) are intrinsically proinflammatory. The objective of the current study was to characterize the inflammatory profiles of AECs from children with CF compared with cells from healthy control subjects. We obtained AECs from healthy children (12) and children with CF (27). Biochemical and functional characteristics were assessed by stimulating cells with IFNÎ³, LPS, a cocktail referred to as cytomix, which consists of IFNÎ³, IL-1Î², TNF-Î±, and LPS, or with human rhinovirus (HRV). Cytokine production was assessed using ELISA. Apoptotic responses to HRV infection were measured via production of single-stranded DNA. Our results indicated that CF andhealthy cells exhibited similarmorphologyin monolayer culture. CF cells constitutively produced greater amounts of IL-6, IL-1Î², and prostaglandin E2, but similar levels of IL-8 and soluble intracellular adhesion molecule-1 compared with healthy cells, and this profile was maintained through repeated passage. Stimulation with LPS or cytomix elicited similar levels of IL-8 in CF and non-CF cells. In contrast, exposure to HRV1b resulted in a marked increase in IL-8 production from CF compared with non-CF cells. CF cells also exhibited reduced apoptosis and increased viral replication compared with non-CF cells after exposure to HRV1b.Weconclude that CF and healthy AECs have similar basal and stimulated expression of IL-8 in response to proinflammatory stimuli, but elevated IL-8 release in response to HRV infection. The elevated IL-8, together with dampened apoptotic responses by CF cells to HRV, could contribute to augmented airway inflammation in the setting of recurrent viral infections early in life.